2021
DOI: 10.32526/ennrj/19/2020230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Lockdown on Air Quality: Evidence from South Asian Megacities

Abstract: Anthropogenic activities were greatly restricted in many South Asian cities during the COVID-19 (Coronavirus disease-2019) pandemic creating an opportunity to observe source reduction of air pollutants. This study analyzed the change in columnar nitrogen dioxide (NO2) and particulate matter (PM2.5, aerodynamic diameter ≤2.5 µm) in five megacities of South Asian countries (Delhi, Dhaka, Kathmandu, Kolkata, and Lahore) from April 1 - May 31 over the previous three years (2018-2020). The Dutch-Finnish Ozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Comparison of two sites in Lahore showed that both experienced high concentrations, but the more central, commercial site had lower concentrations than the residential/industrial site to the south. Finally, a study of OMI columns during the COVID-19 lockdowns for the four cities in our study plus Kathmandu found significant reductions in all five, but the plots also show that the urban signatures are more diffuse in the OMI retrievals than in the TROPOMI retrievals [35].…”
Section: Introductionmentioning
confidence: 44%
“…Comparison of two sites in Lahore showed that both experienced high concentrations, but the more central, commercial site had lower concentrations than the residential/industrial site to the south. Finally, a study of OMI columns during the COVID-19 lockdowns for the four cities in our study plus Kathmandu found significant reductions in all five, but the plots also show that the urban signatures are more diffuse in the OMI retrievals than in the TROPOMI retrievals [35].…”
Section: Introductionmentioning
confidence: 44%